Research on impact characteristics of screening coals on vibrating screen based on discrete-finite element method. Issue 16 (17th August 2020) - Wang, Zhenqian; Peng, Liping; Zhang, Chenglei; Qi, Lin; Liu, Chusheng; Zhao, Yuemin
ABSTRACT: Screening is used extensively for the size classification of coals. During the screening process, the impact of oversized material often causes damage to the screen surface, which then affects the reliability of the vibrating screen. In this study, an orthogonal experiment was designed, and the influence of vibration parameters on impact force was determined using range and variance analysis. The analysis results indicate that the impact force decreases as the amplitude, frequency, and inclination angle increase, and increases as the vibration direction angle increases. The effect of each factor on the impact force within the level range is in the decreasing order: inclination angle, vibration direction angle, frequency, and amplitude. The influence of inclination angle on the impact force is highly significant, vibration direction angle is significant, while the frequency and amplitude are not significant. Therefore, increasing amplitude and decreasing vibration direction angle are the effective ways to reduce the impact force. In order to determine the response of the screen surface under impact, data coupling of discrete-finite element method (DEM-FEM) was performed, and the stress and deformation of the screen surface under a full load were obtained. The results show that the areas of highest stress and largest deformation of the screen surface are mainly located at the blanking position and discharge end. According to the analysis of the DEM-FEM results, the arrangement of the supporting beams was optimized. Compared with a traditional uniform arrangement, the maximum stress of the screen surface decreases by 2.884%, the maximum deformation decreases by 55.952%, the bearing of the screen surface is more uniform and reasonable, and these provide reference points for the design of a vibrating screen.